Thermo-hydro-mechanical analysis of a full-scale heating test. Issue 2 (9th June 2016) - Jacinto, Abel Carlos; Ledesma, Alberto
Abstract : This paper describes the performance, observations and interpretation of the Temperature Buffer Test, a full-scale field experiment simulating repository conditions for high-level radioactive waste. The overall objective of the project was to investigate how well the bentonite buffer blocks can endure the high temperatures expected to be found around vitrified waste canisters. In the experiment, two individually powered heaters were emplaced vertically on top of each other in a pit excavated in crystalline rock and simulated the heat production of radioactive waste. The heaters were surrounded by bentonite hollow cylindrical blocks (the buffer). Extensive instrumentation of the test gave information about the thermo-hydro-mechanical (THM) behaviour of the near-field region constituted by the compacted bentonite buffer surrounding the heater and the immediately crystalline bedrock. Interpretation of experimental results was assisted by the performance of a coupled numerical analysis based on a formulation that incorporates the relevant THM phenomena. Special attention was paid to the progress of hydration in the barrier, to the effects of heating and vapour transport and to the development of swelling pressures in the barrier. The analysis has proven the capability of the numerical formulation to provide reasonable predictive capacity of the main physical processes involved.